PENGARUH INCOME SHIFTING INCENTIVES DAN PENGGUNAAN AUDITOR TERHADAP PENGHINDARAN PAJAK - Turwanto Turwanto; Fendy Ardiansyah Alfan (Direktorat Jenderal Pajak, 2022)
This research aims to examine the association between a different type of income shifting incentives and auditor utilization and corporate tax avoidance in Indonesia. These income shifting incentives include multinationality, transfer pricing aggressiveness, thin capitalization, and intangible assets. We analyse manufacturing companies listed in the Indonesia Stock Exchange during 2014 to 2017 replicating Taylor and Richardson (2012) and Richardson and Taylor (2015) models. We adjust the variable of these models due to data availability. This study uses two models, namely first model using abnormal BTD and second model using BTD as the proxy for tax avoidance. First model suggests that that thin capitalization, multinationality, and intangible assets have a positive effect on tax avoidance. Similarly, the second model shows that thin capitalization, transfer pricing aggressiveness, and intangible assets are positively related to tax avoidance. Conversely, both models indicate that, hiring Big Four Public Accountant Firms bear no significant effect on the level of corporate tax avoidance.